(untitled) (Journal of the College of Basic Education, 2019)
Abstract: In this paper, we introduced new types of open sets which we called p*open set and semi p*open set. Besides, we get the following results: Every open set is p*open and semi p*open. Examples are given to show that the converse may not be true . Preopen set and p*open set are equivalent. Every semi p*open set is semi p open set.